Upaya Mengatasi Kesulitan Menulis Permulaan Pada Siswa Kelas Rendah di SDN 121/I Muara Singoan - Ullyl Khoyrul Ummah; Cahya Karinna; Nabilla Najwa Azzahra; Erwin Efendi Hutagalung; Ayatullah Muhammadin Al Fath (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
This study aims to describe the difficulties in early writing among second-grade students and the teacher’s efforts to overcome them at SDN 121/I Muara Singoan. This research employs a qualitative approach with a descriptive design. Data collection techniques include observation, interviews, and documentation. The results show that students are generally able to write, but still experience difficulties in letter formation, neatness, and accuracy in writing words. The contributing factors include lack of practice, improper learning habits, and limited support at home. The teacher’s efforts include vocabulary-based learning, providing writing examples, step-by-step exercises, and individual guidance. The teacher also provides motivation and conducts continuous evaluation. These efforts are helpful, although some challenges remain in their implementation. Therefore, it is necessary to develop more varied instructional strategies to improve students’ writing skills optimally.